The patient ‘must find his own way’: public policies concerning access to medicines in Angola - Elisa Dulce João Fundanga Calipi; Fernanda Manzini; Leandro Ribeiro Molina; Silvana Nair Leite (Journal of Pharmaceutical Policy and Practice)
Background This study analyses public policies concerning access to medicines and pharmaceutical services in Angola from the right to health perspective. Angola, located in the Western Region of Southern Africa, gained independence in 1975, but the regulation of pharmaceutical activity was enacted only in 2010. Despite these policies, health policies alone do not guarantee the right to health.Methods This qualitative research involves documentary analysis, participant observation, and interviews, utilising theoretical frameworks on access to medicines, health systems, and sociotechnical systems. The analysis framework is organised into three domains: legal rights and obligations, good governance, and service implementation. Data from documentary analysis and field research were categorised within these domains.Results The findings indicate that the regulatory framework acts as a ‘letter of intent’, as legal guarantees are vague and lack clarity regarding responsibilities and resource allocation. Additional weaknesses include indecipherable financing, centralised management, cultural barriers, lack of transparency, and limited recognition of the right to access medicines among health professionals. These issues are further exacerbated by Angola's political-economic structure, external dependence on medicines, and insufficiently trained human resources.Conclusion To enhance access to necessary medicines and services, investment in the education of health professionals and training for community leaders is essential. Public policies regarding access to medicines in Angola are still incipient; therefore, improving drug policy and pharmaceutical services is crucial to ensure access within the framework of the right to comprehensive health care.